NT157 exhibits antineoplastic effects by targeting IRS and STAT3/5 signaling in multiple myeloma - Gustavo Nery de Queiroz; Keli Lima; Livia Bassani Lins de Miranda; Eduardo Magalhães Rego; Fabiola Traina; João Agostinho Machado-Neto (Hematology, Transfusion and Cell Therapy)
Multiple myeloma (MM) is a prevalent hematological malignancy with high recurrence and no definitive cure. The current study revisits the role of the IGF1/IGF1R axis in MM, introducing a novel inhibitor, NT157. The IGF1/IGF1R pathway is pivotal in MM, influencing cell survival, proliferation, and migration and impacting patient survival outcomes. NT157 targets intracellular proteins such as IRS and STAT proteins and demonstrates antineoplastic potential in hematological malignancies and solid tumors. In the present study, we assessed IGF1R signaling-related gene expression in MM patients and healthy donors, unveiling significant distinctions. MM cell lines displayed varying expression patterns of IGF1R-related proteins. A gene dependence analysis indicated the importance of targeting receptor and intracellular elements over autocrine IGF1. NT157 exhibited inhibitory effects on MM cell viability, clonal growth, cell cycle progression, and survival. Moreover, NT157 reduced IRS2 expression and STAT3, STAT5, and RPS6 activation and modulated oncogenes and tumor suppressors, fostering a tumor-suppressive molecular profile. In summary, our study demonstrates that the IGF1/IGF1R/IRS signaling axis is differentially activated in MM cells and the NT157’s capacity to modulate crucial molecular targets, promoting antiproliferative effects and apoptosis in MM cells. NT157 may offer a multifaceted approach to enhance MM therapy.